Renal Sinus Lipomatosis in Transplanted Kidneys: An Unusual Clinical Case - Luca Apicella; Gianfranco Vallone; Sossio Vitale; Gianluca Garofalo; Luigi Russo; Riccardo Gallo; Stefano Federico; Massimo Sabbatini (Case Reports in Transplantation)
Renal sinus lipomatosis (RSL) represents an abnormal proliferation of the adipose tissue surrounding the renal pelvis of uncertain origin, associated with aging, obesity, steroid excess, infections, and calculosis. It represents a rare complication in transplanted kidneys, and, despite the accurate and prolonged radiological followup of transplanted organs, only a few cases of RSL have been described in graft recipients, with no remarkable effects on renal function. The diagnosis relies on ultrasonography (US), magnetic resonance imaging (MRI), computed tomography (CT), and, finally, percutaneous biopsy. We describe the case of an extensive RSL in a 38-year-old renal transplant recipient, diagnosed by ultrasonography and computed tomography. The patient underwent a radiologic study because of an acute, asymptomatic renal impairment, that led to the diagnosis of a RSL of unusual dimensions, associated with a discrete hydronephrosis. Paradoxically, after a short course of steroids, the recovery of renal function and the partial resolution of calyceal dilatation were observed. The rarity of this affection, the need of a differential diagnosis with fat-containing tumors, and the possibility of parenchymal inflammation associated with RSL, potentially responsive to steroids, are also discussed.